HUBUNGAN PERSEPSI SISWA TERHADAP PELAJARAN MATEMATIKA DENGAN HASIL BELAJAR MATEMATIKA DI KELAS V SD NEGERI 194 PEKANBARU - Sherly Mardiani; Gustimal Witri; Jaya Adi Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the relationship of students' perceptions of mathematics with learning outcomes in class V SD Negeri 194 Pekanbaru. The hypothesis of this study is that there is a positive and significant relationship between students' perceptions of mathematics lessons with mathematics learning outcomes in class V SD Negeri 194 Pekanbaru. This type of research used in this research is quantitative research with correlational research methods. This research was conducted in 194 Pekanbaru Elementary School with a population of 132 people and a sample of 132 people. This population is taken from 3 classes namely, class VA, VB, and VC. The instrument used was a closed questionnaire using a Likert scale. Hypothesis testing using the Product Moment correlation test was performed with processed data SPSS version 23. The results showed that there was a positive and significant relationship between students' perceptions of mathematics and student learning outcomes in class V of SD Negeri 194 Pekanbaru. Evidenced by the results of data analysis, the relationship between students 'perceptions of mathematics with students' mathematics learning outcomes obtained rcount of 0.488 which shows that the relationship is in the medium category.Key Words: Student Perception, Learning Outcomes